Therapeutic antibodies: Discovery, design and deployment - Ramsland, Paul; Hutchinson, A.; Carter, P. (Elsevier Ltd, 2015)
Therapeutic antibodies have come of age with major progress being made in cancer, autoimmunity and chronic inflammation, as well as a wide range of other human diseases. Antibody engineering is further driving development of novel antibody formats and genetically modified cell-based therapies that harness the power of the immune system to progress cures in otherwise intractable human diseases. Nevertheless, there are still significant challenges ahead for basic and applied research relating to therapeutic antibodies. This special issue of the journal provides reviews and opinions that relate to the discovery, design and deployment of antibodies as therapeutics.